1998
DOI: 10.1046/j.1365-2141.1998.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing bone marrow micro‐environment during development of acute myeloid leukaemia in rats

Abstract: Summary. The Brown Norwegian rat transplanted with promyelocytic leukaemic cells (BNML) has been used as a model for human acute myeloid leukaemia. We have previously shown that both the blood supply to the bone marrow and the metabolic rate decrease in relation to the leukaemic development in these rats. Here we have investigated how the development and progression of this leukaemia affect oxygenation, pH and proliferation of normal and leukaemic cells in vivo. Bone marrow pH was measured by a needle electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 15 publications
(20 reference statements)
1
57
0
Order By: Relevance
“…Prominent examples include differentiation induction therapy, developed from preliminary studies with cyclic adenosine monophosphate (cAMP) inducing cholera toxin in the BNML and BNML-cholera toxin-resistant models, 161,268 269 circuitously leading to the clinical studies of agents such as theophylline 273 (cAMP induction/stabilisation), Gemtuzumab ozogamicin 274 (conjugated mAb) and granulocyte colony-stimulating factor 275 (G-CSF-cytokine). These results and the application of the BNML rat model in more recent work pertaining to angiogenesis and microenvironmental modifications by Iversen et al [276][277][278][279] rationalise continued interest in this model.…”
Section: Mrd Detection and Treatment In Bnmlmentioning
confidence: 77%
“…Prominent examples include differentiation induction therapy, developed from preliminary studies with cyclic adenosine monophosphate (cAMP) inducing cholera toxin in the BNML and BNML-cholera toxin-resistant models, 161,268 269 circuitously leading to the clinical studies of agents such as theophylline 273 (cAMP induction/stabilisation), Gemtuzumab ozogamicin 274 (conjugated mAb) and granulocyte colony-stimulating factor 275 (G-CSF-cytokine). These results and the application of the BNML rat model in more recent work pertaining to angiogenesis and microenvironmental modifications by Iversen et al [276][277][278][279] rationalise continued interest in this model.…”
Section: Mrd Detection and Treatment In Bnmlmentioning
confidence: 77%
“…Leukemia is cancer of blood cells, and it has been shown that acidic microenvironment is a key feature of exponentially growing cells in bone marrow (Mortensen et al 1998). Especially, acute leukemia is a rapidly progressing disease that results in the accumulation of immature, abnormal cells in the marrow and blood.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 We have used this BNML model extensively to study the bone marrow microenvironment during progression of the leukemic process. [15][16][17] Given these recent observations that angiogenesis might play a role in progression of leukemia, the aim of the present study was to examine if treatment with the anti-angiogenic compounds endostatin and/or PI-88 could arrest the expansion of malignant cell populations in our two experimental models of human myeloid leukemia, the JMML mice and the BNML rats.…”
Section: Introductionmentioning
confidence: 99%